Implementation of international anti-corruption standards in the economic space - Русін, Роман Михайлович; Русін, Р. М.; Русин, Роман Михайлович; Rusin, Roman M.; Дубинський, Олег Юрійович; Дубинський, О. Ю.; Дубинский, Олег Юрьевич; Dubynskyi, Oleh Yu.; Dubinskiy, Oleg; Харитонов, Роман Феліксович; Харитонов, Р. Ф.; Харитонов, Роман Феликсович; et al. (Baltija Publishing, 2021)
Corruption as an anti-social phenomenon was initially considered in the moral, social and legal dimension. It was not until the 1970s that corruption began to be studied as an economic category and became a subject of systemic economic analysis. It should be emphasized that in legal practice, corruption is most often interpreted as a socially dangerous illegal phenomenon, which is a consequence of blackmail, bribery, venality of officials that use their authority for personal enrichment, disregarding the interests of other members of society. Therefore, corruption is usually seen as a type of offense and criminal actions of officials in contradiction to the interests of the state and its citizens. And anti-corruption measures are associated with the improvement of the current legislation in terms of ensuring the inevitability of responsibility for corruption and corruption-related offenses. At the same time, given that corruption is inseparable from the shadow economy, it is necessary to study these two phenomena as a single system and consider anti-corruption policy as a key component of the fight against the shadow economy. The world community, in particular the EU, has a well-developed system of state regulation, which many countries are guided by. Despite this, the budgets of EU countries lose a certain amount each year from corruption schemes in the economic sphere. The aim of the article is to study the theoretical and institutional foundations of anti-corruption policy as a component of the fight against shadow economy to update the powers of relevant authorities in terms of their implementation in international anti-corruption standards in the economic space. In Ukraine, anti-corruption policy is implemented in the context of the creation of an institutional system to prevent and combat corruption, which includes specialized organizations, legislation, the formation of special mechanisms to prevent and combat corruption, etc. At present, the following bodies have already been established and are functioning in Ukraine: National Agency on Corruption Prevention (NACP), National Anti-Corruption Bureau of Ukraine (NABU), Specialized Anti-Corruption Prosecutor's Office (SAPO), Asset Recovery and Management Agency, High Anti-Corruption Court of Ukraine, and some tasks in the field of combating corruption are performed by the prosecutor's office and the National Police of Ukraine. The State Financial Monitoring Service of Ukraine collects, analyzes and publishes information on suspected cases of withdrawal of funds of possible criminal origin. The results of the conducted research indicate that most of the goals set by the Anti-Corruption Strategy for 2014-2017 were not achieved in the previous years. Consequently, measures should continue to be taken both to increase the effectiveness of institutional mechanisms for preventing and countering corruption and to eliminate corruption risks in different sectors (primarily those where there is a high experience of corruption and/or the worst perception of corruption of the institutions involved). The combination of both approaches can give the greatest result in reducing the level of corruption in the coming years, so this is the basis of the proposed draft concept of anti-corruption policy for 2020-2024. The implementation of international standards contributed both to the development of the system of prevention and counteraction to corruption (including specialized institutions) and to the reduction of corruption in some sectors by eliminating corruption risks, which were systemic and structural in nature. Further implementation of these commitments and intentions will have a positive impact on reducing corruption and demonstrates the political will at all levels to achieve tangible results of implementing anti-corruption policies.

Корупція як антисоціальне явище спочатку розглядалася в моральному, соціальному та правовому вимірі. Лише в 1970-х роках корупцію почали вивчати як економічну категорію і вона стала предметом системного економічного аналізу. Слід підкреслити, що в юридичній практиці корупція найчастіше трактується як суспільно небезпечне протиправне явище, що є наслідком шантажу, підкупу, продажності посадових осіб, які використовують свої повноваження для особистого збагачення, нехтуючи інтересами інших членів суспільства. Тому корупцію зазвичай розглядають як вид правопорушень і злочинних дій посадових осіб, що суперечать інтересам держави та її громадян. А антикорупційні заходи пов’язані з удосконаленням чинного законодавства в частині забезпечення невідворотності відповідальності за корупційні та пов’язані з корупцією правопорушення. Водночас, зважаючи на те, що корупція невіддільна від тіньової економіки, необхідно вивчати ці два явища як єдину систему та розглядати антикорупційну політику як ключову складову боротьби з тіньовою економікою. Світове співтовариство, зокрема ЄС, має добре розвинену систему державного регулювання, якою керуються багато країн. Незважаючи на це, бюджети країн ЄС щороку втрачають певну суму від корупційних схем в економічній сфері. Метою статті є дослідження теоретичних та інституційних засад антикорупційної політики як складової боротьби з тіньовою економікою для оновлення повноважень відповідних органів влади в частині їх імплементації у міжнародні антикорупційні стандарти в економічному просторі. В Україні антикорупційна політика реалізується в контексті створення інституційної системи запобігання та протидії корупції, яка включає спеціалізовані організації, законодавство, формування спеціальних механізмів запобігання та протидії корупції тощо. В Україні вже створені та діють органи: Національне агентство з питань запобігання корупції (НАЗК), Національне антикорупційне бюро України (НАБУ), Спеціалізована антикорупційна прокуратура (САП), Агентство з питань стягнення та управління активами, Вища антикорупційна прокуратура, Корупційний суд України, а окремі завдання у сфері протидії корупції виконує прокуратура та Національна поліція України. Державна служба фінансового моніторингу України збирає, аналізує та публікує інформацію про підозрювані випадки вилучення коштів можливого злочинного походження. Результати проведеного дослідження свідчать про те, що більшість цілей, визначених Антикорупційною стратегією на 2014-2017 роки, не були досягнуті в попередні роки. Отже, слід продовжувати вживати заходів як для підвищення ефективності інституційних механізмів запобігання та протидії корупції, так і для усунення корупційних ризиків у різних сферах (насамперед у тих, де є високий досвід корупції та/або найгірше сприйняття корупції з боку державних органів). Поєднання обох підходів може дати найбільший результат у зниженні рівня корупції в найближчі роки, тому саме на цьому базується запропонований проект концепції антикорупційної політики на 2020-2024 роки. Впровадження міжнародних стандартів сприяло як розвитку системи запобігання та протидії корупції (у тому числі спеціалізованим установам), так і зниженню рівня корупції в окремих сферах шляхом усунення корупційних ризиків, які мали системний та структурний характер. Подальша реалізація цих зобов’язань і намірів позитивно вплине на зниження рівня корупції та продемонструє політичну волю на всіх рівнях для досягнення відчутних результатів реалізації антикорупційної політики.
Rusin R. Implementation of international anti-corruption standards in the economic space / R. Rusin, O. Dubinskiy, R. Kharytonov // Baltic journal of economic studies. - Vol. 7. - Iss. 5. - Baltija Publishing, 2021. - Р. 184-191.
Keywords: corruption; anti-corruption policy; international standards; anti-corruption bodies; implementation of legislation; anti-corruption strategy; корупція; антикорупційна політика; міжнародні стандарти; антикорупційні органи; імплементація законодавства; антикорупційна стратегія; Research Subject Categories::LAW/JURISPRUDENCE